An Evaluation of Profiles for Disk Cams with In-line Roller Followers - M. S. M., Sani; M. M., Rahman; Zamzuri, Hamedon; M. M., Noor; M. R. M., Rejab; K., Kadirgama (2008)

(untitled)
This paper presents an evaluation of graphical method and experimental work for determining disk cam profiles. The procedures are mainly accurate for obtaining points on a cam with roller followers. For both analysis procedures, the coordinates of the centre of the follower are required at small increments of the cam angle. Both procedures can be easily programmed and depend only on the follower coordinates and not the follower type. A comparison on motion analysis has been made to determine the percentage error occurred in both procedures.